2007
DOI: 10.4049/jimmunol.178.7.4557
|View full text |Cite
|
Sign up to set email alerts
|

Infection with a Helminth Parasite Prevents Experimental Colitis via a Macrophage-Mediated Mechanism

Abstract: The propensity of a range of parasitic helminths to stimulate a Th2 or regulatory cell-biased response has been proposed to reduce the severity of experimental inflammatory bowel disease. We examined whether infection with Schistosoma mansoni, a trematode parasite, altered the susceptibility of mice to colitis induced by dextran sodium sulfate (DSS). Mice infected with schistosome worms were refractory to DSS-induced colitis. Egg-laying schistosome infections or injection of eggs did not render mice resistant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
237
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 253 publications
(248 citation statements)
references
References 55 publications
6
237
2
Order By: Relevance
“…Thus, cystatin-treated macrophages resembled type II-activated macrophages (42). Just recently it has been shown that infection with the trematode parasite S. mansoni prevents experimental colitis via a macrophage-mediated mechanism (43). We are currently studying the molecular mechanisms of immune modulation by filarial cystatin, such as the signaling pathways involved and the domains of cystatin responsible for the described effects.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, cystatin-treated macrophages resembled type II-activated macrophages (42). Just recently it has been shown that infection with the trematode parasite S. mansoni prevents experimental colitis via a macrophage-mediated mechanism (43). We are currently studying the molecular mechanisms of immune modulation by filarial cystatin, such as the signaling pathways involved and the domains of cystatin responsible for the described effects.…”
Section: Discussionmentioning
confidence: 99%
“…1 Collectively, these studies have shown that as a consequence of the host response to infection with helminth parasites, there is mobilization of transforming growth factor (TGF)-␤, interleukin (IL)-10, Foxp3 ϩ regulatory T cells, alternatively activated macrophages, and inhibition of IL-17-and interferon (IFN)-␥-driven events: one, or a combination, of these events could block the development of autoimmune and inflammatory disorders. [2][3][4][5][6][7] These findings have been complemented by intriguing data suggesting that infection with viable parasitic nematodes could be a treatment for patients with inflammatory bowel disease (IBD) 8 or asthma, 9 whose condition is not managed by conventional therapies.…”
mentioning
confidence: 87%
“…and P.J.) blinded to the time point, strain, and treatment groups, as per published methods (28,29).…”
Section: Methodsmentioning
confidence: 99%